Reliance Commercial Corporation—first sign board - Reliance Industries Limited (2022)
In February 1958, Shri Dhirubhai Ambani started Reliance Commercial Corporation in partnership with Shri Trambhakbhai Damani. When asked why he chose to name his company Reliance, Shri Dhirubhai Ambani said, 'I saw it written somewhere and it stayed in my mind.'